How does carbon tax affect social welfare and emission reduction in Finland? - Mojtaba Khastar (Energy Reports, 2020)
Environmental concerns related to fossil fuels utilization has developed different energy/environmental policy tools that Carbon tax is one of the important ones. There are huge debates among different political parties related to the positive and negative effects of the carbon tax on the energy and environmental policies of the countries. However, carbon tax not only can have effects on the utilization and consumption of energy sources portfolios, but it may also have negative or positive effects on the economy, industry, and social welfare of the countries that should be identified and analyzed, in particular for countries with high energy-intensive industries such as Finland. The purpose of this research is to answer the question: “How does Carbon Tax affect social welfare and emission reduction in Finland?” We use the computable general equilibrium model to analyze the impact of the carbon tax on social welfare and the rate of emission reduction. Considering the fact that Finland has several years of carbon tax policy application background, evaluation of the impact of this policy on Finland’s social-environmental structure is very valuable for other countries, especially newcomers. Our results show that despite carbon tax policy in Finland has been successful in the reduction of carbon dioxide emissions, however, it has negative effects on the social welfare of Finns. Therefore, an optimum level of the carbon price is recommended for future policy revision